Inoperable aortic stenosis in the elderly: benefit from percutaneous transluminal valvuloplasty. Issue 6564 (10th January 1987) - Jackson, G; Thomas, S; Monaghan, M; Forsyth, A; Jewitt, D
Abstract : Eight patients with severe symptomatic calcific aortic stenosis were considered to be unsuitable for valve replacement. Four were admitted with pulmonary oedema and three in cardiogenic shock and one had angina at rest. With the use of echocardiographic and radiographic guidance percutaneous transluminal aortic valvuloplasty was carried out. Aortic gradients were reduced by an average of 40%. All four patients who presented with cardiac failure improved immediately and remained well six months later. The patient with angina was symptom free at nine months. Two of the three patients who presented in cardiogenic shock improved immediately and were well nine and three months later. The other patient died four hours after the procedure. Doppler echocardiographic studies showed a slight initial increase in aortic incompetence, but this did not worsen and valvar gradients remained improved three and six months later. Percutaneous valvuloplasty of the aortic valve is an effective therapeutic option in patients with severe calcific aortic stenosis who are unfit for surgery. Its role as an alternative to surgery has not been considered and should be investigated in a controlled clinical trial.